Life Table Studies of Helicoverpa Armigera Hubner: A Review on Recent Works Done in India - Banna Ushasri; Sarma, Arup; Surashmi Bhattacharyya; Hiranya DevaNath (Andalasian International Journal of Entomology, 2025)
For demographic studies of organisms, life tables are one of the most appropriate tools that help in presenting the patterns of birth, death, survival of progeny and also the life expectancy. Life tables can be constructed based on the sexes in relation to the ecological drivers that include both biotic and abiotic factors. Helicoverpa armigerais a highly destructive pest affecting the major food crops such as pulses, fruit crops, oilseeds etc. all over the world. In India it is cosmopolitan. The estimated yield loss in India is about nearly 38%. An attempt has been made here to review the information generated in some recent works regarding the population studies of this polyphagous pest and its management in India.